The hacker and the state : cyber attacks and the new normal of geopolitics - Buchanan, Ben (Writer on cybersecurity), (Cambridge, Massachusetts : Harvard University Press, 2020)
"The threat of cyberwar can feel like something out of a movie: nuclear codes hacked, powerplants melting down, immediate crisis. In reality, state-sponsored hacking looks nothing like this. It's covert, insidious, and constant. Ben Buchanan reveals the cyberwar that's already here, reshaping the global contest for geopolitical advantage"-- Includes bibliographical references and index. Part one. Espionage: Exploiting home-field advantage -- Defeating encryption -- Building a backdoor -- Strategic espionage -- Counterintelligence -- Part two. Attack: Strategic sabotage -- Targeted disruption -- Coercion -- Testing and demonstration -- Part three. Destabilization: Election interference -- Exposure -- Theft, ransom, and manipulation -- Widespread disruption. "The threat of cyberwar can feel like something out of a movie: nuclear codes hacked, powerplants melting down, immediate crisis. In reality, state-sponsored hacking looks nothing like this. It's covert, insidious, and constant. Ben Buchanan reveals the cyberwar that's already here, reshaping the global contest for geopolitical advantage"--